Cover Image. (13th March 2018) - Haymerle, G.; Enzenhofer, E.; Lechner, W.; Stock, M.; Schratter‐Sehn, A.; Vyskocil, E.; Bachtiary, B.; Selzer, E.; Erovic, B.M.
Abstract : The cover image, by G. Haymerle et al., is based on the Correspondence The effect of adjuvant radiotherapy on radial forearm free flap volume after soft palate reconstruction in 13 patients, DOI10.1111/coa.13042 .